Metacommunity structuring in Himalayan streams over large elevational gradients: the role of dispersal routes and niche characteristics. (22nd October 2016) - Tonkin, Jonathan D.; Tachamo Shah, Ram Devi; Shah, Deep Narayan; Hoppeler, Felicitas; Jähnig, Sonja C.; Pauls, Steffen U.
Abstract: Aim: To examine metacommunity structuring in stream communities over large elevational gradients by disentangling physical and environmental structuring and the importance of different dispersal routes and niche characteristics. Location: Headwater streams in three catchments in the Hindu‐Kush Himalaya of central and eastern Nepal. Methods: We explored metacommunity structuring of stream invertebrates (including deconstructed assemblages by niche position and breadth) using a combination of approaches, including the elements of metacommunity structure and distance–decay relationships. We compared the importance of dispersal routes, elevation and local environmental conditions through five distance matrices: Euclidean, topographic, river network, elevational and environmental. Results: Communities were structured along the elevational gradient with clear turnover apparent in two catchments, with Clementsian (compartmentalized) and Gleasonian (individualistic) distributions. Local environment played a minor role, and the selected distance matrices (i.e. elevation, three physical distances and environment) varied between catchments and niche groups. Contrary to expectation, specialists were more spatially than environmentally controlled, potentially reflecting dispersal limitation. Main conclusions: In these physically dominated systems, local environment was overridden by dispersal limitation, particularly when considering specialists. Where barriers were not limiting dispersal, niche sorting along the elevational gradients represented the key structuring force. Overall, our findings reveal the importance of elevation and the spatial arrangement of sites in structuring metacommunities. We emphasize the value of considering physical structuring and spatial extent in modulating species sorting in metacommunities.